SIGNIFIKANSI GAMBAR TERHADAP PEMAHAMAN TEKS INSTRUKSI BAHASA INGGRIS PADA PENDIDIKAN VOKASI - Mahlil Mahlil; Tanzir Masykar (VOCATECH: Vocational Education and Technology Journal, 2020)
Abstract One of the skills vocational education students must master in English courses is understanding the language of instruction or procedures in English. A total of 24 vocational education students at the Politeknik Negeri Lhokseumawe participated in filling out the questionnaires distributed online. Data were collected using the convenience sampling technique for two weeks from the date of August 26, 2020 until September 9, 2020. The data were analyzed qualitatively using the Miles and Huberman model. Data analysis consists of four stages, extensive coding, pattern coding, distilling and making propositions. The results showed that the majority of vocational education students at PNL were visual learners. The inclusion of pictures in the English instruction material is very helpful in understanding the text of the instructions given. Students prefer English instruction materials that are equipped with pictures rather than just pictures or just text. Students also use google translate to understand unfamiliar words to understand English instruction texts. Keywords: English, Language Instruction, Picture Signifiance, Vocation __________________________ Abstrak Salah satu kemampuan yang harus dikuasai oleh mahasiswa pendidikan vokasi dalam mata kuliah Bahasa Inggris adalah memahami bahasa instruksi atau prosedur berbahasa Inggris. Sebanyak 24 mahasiswa pendidikan vokasi pada kampus Politeknik Negeri Lhokseumawe berpartisipasi mengisi kuesioner yang disebarkan secara daring. Pengambilan data menggunakan the convenience sampling technique selama dua minggu dari tanggal 26 Agustus 2020 sampai 9 Sepetember 2020.Data dianalisis secara kualitatif dengan menggunakan model Miles dan Huberman. Analisa data terdiri dari empat tahap, extensive coding, pattern coding, distilling and making propositions. Hasil penelitian menunjukkan bahwa mayoritas mahasiswa pendidikan vokasi di PNL adalah pembelajar visual. Penyertaan gambar pada materi instruksi berbahasa Inggris sangat membantu memahami teks instruksi yang diberikan. Siswa lebih memilih materi instruksi berbahasa Inggris yang dilengkapi dengan gambar daripada hanya gambar atau hanya teks saja. Mahsiswa juga menggunakan bantuan google translate dalam memahami teks instruksi Bahasa Inggris yang sulit dipahami. Kata Kunci: Bahasa Instrucksi, Bahasa Inggris, Sigifikansi Gambar, Vokasi __________________________